Exercise training in obese older adults prevents increase in bone turnover and attenuates decrease in hip BMD induced by weight loss despite decline in bone-active hormones - Shah, Krupa (2011)
Weight-loss therapy to improve health in obese older adults is controversial because it causes further bone loss. Therefore, it is recommended that weight-loss therapy should include an intervention to minimize bone loss such as exercise training (ET). The purpose of this study was to determine the independent and combined effects of weight loss and ET on bone metabolism in relation to bone mineral density (BMD) in obese older adults. One-hundred-seven older (age >65 yrs) obese (BMI ≥30 kg/m(2)) adults were randomly assigned to a control group, diet group, exercise group, and diet-exercise group for 1 year. Body weight decreased in the diet (−9.6%) and diet-exercise (−9.4%) groups, not in the exercise (−1%) and control (−0.2%) groups (between-group P<.001). However, despite comparable weight loss, bone loss at the total hip was relatively less in the diet-exercise group (−1.1%) than in the diet group (−2.6%), whereas BMD increased in the exercise group (1.5%) (between-group P<.001) Serum C-terminal telopeptide (CTX) and osteocalcin concentrations increased in the diet group (31% and 24%) while they decreased in the exercise group (−13% and −15%) (between-group P<.001). In contrast, similar to the control group, serum CTX and osteocalcin concentrations did not change in the diet-exercise group. Serum procollagen propeptide concentrations decreased in the exercise group (−15%) compared with the diet group (9%) (P=.04). Serum leptin and estradiol concentrations decreased in the diet (−25% and −15%) and diet-exercise (−38% and −13%) groups, not in the exercise and control groups (between-group P=.001). Multivariate analyses revealed that changes in lean body mass (β=.33), serum osteocalcin (β= −.24), and 1-RM strength (β=.23) were independent predictors of changes in hip BMD (all P<.05). In conclusion, the addition of ET to weight-loss therapy among obese older adults prevents weight-loss-induced increase in bone turnover and attenuates weight-loss-induced reduction in hip BMD despite weight-loss-induced decrease in bone-active hormones.